ANALISIS BEBAN KERJA GURU DALAM PERSPEKTIF ISLAM - Ningsih, Fitri Ayu; Fasa, Muhammad Iqbal; Suharto, Suharto (Jurnal Ilmiah Pendidikan dan Keislaman, 2022)
The teacher is an important element in the learning process. The role and function of the teacher is to educate the lives of the nation's children. The demands of the main tasks and functions of teachers to educate the nation's children become a workload for the teachers themselves. Mental workload is influenced by several factors such as internal and external factors. Internal factors, for example, excessive work demands, frustration will arise in carrying out their duties. When the teacher feels frustrated, it will have an impact on the teacher's declining performance. External factors such as the outbreak of the COVID-19 virus that hit the whole world, had a very significant impact on the world of education. Teachers and students are required to apply new patterns to the learning system. Learning from home is a new learning system that must be applied during the COVID-19 pandemic. The learning system from home requires teachers to work more extra than before. That's all because teachers or students are not used to doing the learning system from home